2019
DOI: 10.3390/ani9070429
|View full text |Cite
|
Sign up to set email alerts
|

Does Virtual Fencing Work for Grazing Dairy Cattle?

Abstract: Pasture management in Australia’s dairy industry requires the manual shifiting of temporary electric fences to maintain pasture quality and growth. Virtual fencing presents an alternative to save time and labour costs. We used automated virtual fence (VF) collars to determine the variation in learning of the virtual fence stimuli, and evaluated the success of the technology to contain cows in a predetermined area of pasture. Twelve Holstein-Friesian non-lactating multiparous dairy cows were fitted with the col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
68
3
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 19 publications
11
68
3
6
Order By: Relevance
“…While individual testing increases scientific understanding of the factors that may affect the adoption of virtual fencing technology, it does not provide an applied understanding of the overall effectiveness of the technology. Recent research has shown that groups of 12 dry dairy cattle being grazed at low stocking densities using virtual fencing technology remain in the inclusion zone 99% of the time [14]. As discussed by Campbell et al [3], cattle are gregarious species and their behaviour when tested individually may not relate to their behaviour in a herd.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While individual testing increases scientific understanding of the factors that may affect the adoption of virtual fencing technology, it does not provide an applied understanding of the overall effectiveness of the technology. Recent research has shown that groups of 12 dry dairy cattle being grazed at low stocking densities using virtual fencing technology remain in the inclusion zone 99% of the time [14]. As discussed by Campbell et al [3], cattle are gregarious species and their behaviour when tested individually may not relate to their behaviour in a herd.…”
Section: Discussionmentioning
confidence: 99%
“…The ethical acceptability of virtual fencing technology relies on the ability of all animals to learn the association between audio and electrical stimuli and through this gain a level of predictability and controllability over their environment [1]. Virtual fencing could enable the implementation of increasingly intense and complex grazing regimes in pastoral dairy systems [13,14], and with increased complexity comes a potential risk of some animals not learning to avoid the electrical stimulus [1]. Long-term studies with larger group sizes are needed to determine if all animals are able to learn the association between the audio and electrical stimulus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Virtual fencing systems rely on operant conditioning, positive punishment associative learning between a conditioned stimulus (an audio tone, AT) and unconditioned stimulus (an electrical pulse, EP) [ 5 ] administered to an animal via neck-mounted devices [ 6 , 7 ]. Positive punishment associative learning training method utilises a negative/aversive stimulus to alter an animals behaviour to avoid receiving the stimuli [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Though some arguments have been raised with respect to the effectiveness of geo-fencing, such as in the work of [47], rather than purely depending on stimuli, UAVs can be used to steer the animals back into range when they roam out of grazing perimeters. UAVs can therefore provide a cheap and effective way of getting animals back "inline" and are particularly useful when a number of animals stray outside different ends of the perimeter.…”
Section: Geo-fencing and Virtual Perimetermentioning
confidence: 99%